MANAGEMENT OF VILLAGE FUND ALLOCATION FROM APBN AND ITS IMPACT ON VILLAGE ECONOMIC GROWTH IN INDONESIAN TERRITORY - Sugiharto Sugiharto; RB Iwan Noor Suhasto (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
So far, development in the village can be said to be underestimated or carried out half-heartedly by the central government as well as by the regional government. This can be seen by the lack of expertise and competence of Human Resources (HR), the less optimal management of natural resources and the lack of value-added economic resources as well as access to infrastructure that is mediocre. This study aims to examine how the level of economic growth in villages in Indonesia after receiving allocation funds from the State Revenue and Expenditure Budget (APBN), where each village receives approximately 1.3 billion funds from the state. This research was conducted by involving the village community based on sampling which was tested by researchers regarding the village funds provided by the state have a significant impact or not on the economic growth of villages in the territory of Indonesia.